Organic geochemistry and petrology of the coals in the Laisong Formation, Naga Schuppen Belt, NE India: Inferences on hydrocarbon potential and depositional environment. Issue 2 (1st October 2021) - Gogoi, Mousumi; Walling, Temsulemba; Thadoju, Satish Kumar; Mathur, Neeraj; Longkumer, Limasanen; Phukan, Sarat
Abstract : The Oligocene Laisong Formation in the Naga Schuppen Belt is coal bearing along the Dimapur‐Kohima Road section, Nagaland. The coals are sulphurous and classified as lignite to sub‐bituminous 'C' based on various rank parameters. The coals are dominantly composed of vitrinite followed by inertinite and liptinite in order of abundance. The coals have high‐quality Type III kerogens derived mainly from angiosperm plants. The richness and quality of organic matter in the coal is excellent to act as a petroleum source rock. Most of the maturity parameters indicate that maturity ranges from immature to early mature. The biomarker parameters and facies critical maceral associations point to deposition of the coal‐bearing strata in non‐marine/terrestrial depositional environment under moist hydrodynamic conditions, possibly in an upper delta plain environment. However, the high sulphur content of the coal points to deposition in a lower delta plain environment. Comparison with other Palaeogene coal deposits of the same sedimentary basin shows that the Laisong coals contain lesser amount of liptinite macerals and much higher amount of sulphur than these deposits. All these deposits are of similar rank, however, the Laisong coals show marginally low thermal maturity from the viewpoint of hydrocarbon generation. Abstract : The low‐rank coals of the Oligocene Laisong Formation, Naga Schuppen Belt, are rich in vitrinite with some inertinite and liptinite. The coals mainly contain Type III kerogen that is derived from angiosperm plants. Most of the maturity parameters indicate that the maturity ranges from immature to early mature from the viewpoint of hydrocarbon generation. The biomarker parameters and faciescritical maceral associations are suggestive of deposition of the coal‐bearing strata in non‐marine/terrestrial depositional environment under moist hydrodynamic condition possibly in an upper delta plain environment. However, rich concentration of sulphur is indicative of lower delta plain environment.